Implementation of emergency-based thrombolysis : an achievable option for rural hospitals in developing countries - SMS, Azarisman; Ngow, Harris Abdullah; PA, Melor; Ab Rahman, Jamalludin; Ahmad, Fauzi@Fauri; S., Sapari; K., Khairi; S., Noorfaizan; Oteh, Maskon (Springer New York LLC, 2008)
Background In developing countries such as Malaysia, the primary mode for revascularization is via thrombolytic therapy. This is only effective when instituted within a small time window and pre-hospital delay is a major concern. In a region where the mean house-to-door times can be as long as 8.5 hours, there is an urgent need to reduce the door-to-needle times. Methods Emergency-based thrombolysis was initiated at Hospital Tengku Ampuan Afzan Kuantan, a 600-bed regional hospital in Malaysia. One hundred and thirty three patients with acute ST elevation myocardial infarction patients were screened. 39 patients were recruited in the 4 months prior to the implementation date and 94 patients were recruited after. The mean house-to-door, door-to-needle times were recorded. Results The majority of patients were male 88.7%, with a mean age of 56.4 10.3 years. The median presentation time (house-to-door) was 117.50 minutes before and 136.00 minutes after (p 0.213, Mann- Whitney U) minutes. The median door-to-needle time was 100.00 minutes before and 50.00 minutes after (p 0.031). The mortality rates were 12.8% before and 11.70% (p0.87, Fisher exact test) after mplementation of Emergency-based thrombolysis. Conclusion Implementation of Emergency-based thrombolysis has markedly improved the door-to-needle times and resulted in a trend towards reduced mortality rates in acute ST-elevation myocardial infarction.